Impacts of Online Banking on Customer Satisfaction in Commercial Banks in the 2nd District of Albay - Abapo, Laurence Bernadette (JPAIR Multidisciplinary Research, 2025)
Online banking has gradually acquired acceptance in today's digital environment. It has become vital to modern financial systems, offering enhanced accessibility, efficiency, and user autonomy. It provides various advantages to people, especially those living far from banks. Digital financial platforms offer convenience, cost savings, eco-friendly, and faster bank transactions. Through this, clients can open accounts, transfer funds, and monitor their savings accounts, current accounts, time deposits, credit cards, and loans. It decreases the need for paper statements and in-person services, supporting sustainability. It saves time, reduces the need to visit bank branches, and is available 24/7. Many platforms offer budgeting tools, spending analysis, and automated savings features. As online banking develops in the Philippines, it also comes with potential challenges many Filipinos might face. This research aimed to determine the challenges encountered in online banking. It also aimed to formulate recommendations and an action plan for online banking services to enhance customer satisfaction. The study used a quantitative research design to analyze and hence boost data validity. The data revealed customer satisfaction levels with online banking services and identified challenges in customer support, security and privacy, accessibility, and transaction speed. By addressing these key areas, commercial banks can improve customer satisfaction and enhance service performance to boost customer loyalty, retention, and competitive positioning in the market. Strengthening the key factors also attracts potential new clients. The researcher also formulated an action plan to maximize the services offered by online banking by the Commercial Banks in the 2nd District of Albay.
Keywords: Business and Management; customer satisfaction; online banking; security and privacy; account management services; customer support; accessibility; commercial banks; quantitative; Philippines